Development and psychometric analysis of a new tool to assess food literacy in diabetic patients - Fatemeh Bastami; Mahnaz Mardani; Pouria Rezapour (BMC Nutrition, 2022)
Abstract Background One of the factors affecting self-care in diabetic patients is food literacy, which helps said patients in following a healthy diet. Thus, it is crucial to analyze food literacy in diabetic patients through suitable and reliable instruments.  Objective The current study aimed to design a questionnaire for food literacy assessment in diabetic patients and analyze its psychometric features. Method The present study was a cross-sectional descriptive analysis carried out in 2021. Firstly, the concepts of food literacy in diabetic patients were identified and the questionnaire was deigned based on them. Secondly, its face and content validities and its reliability were analyzed. Finally, the construct validity was analyzed by exploratory factor analysis. The study was carried out on 300 diabetic participants chosen at random via stratified cluster sampling from Health service centers. The exploratory factor analysis was carried out by extracting the main factors and using varimax rotation with eigenvalue values more than 1. Results A five-pronged structure accounted for 52.745% of food literacy variance. This included the ability to read food facts, practical ability to group foods, the ability to identify the caloric content of different foods, the ability to understand the effect of food on health, and the ability to prepare a healthy meal. Items with an impact score below 1.5 were discarded. Additionally, items with CVR scores below 0.62 and CVI scores below 0.79 were deleted too. The Kaiser-Meyer-Okin measurement was 0.836 (p < 0.001). Alpha Cronbach Scale dimension was 0.610–0.951. Conclusion The results of this study showed that the exploratory dimensions of the current study were consistent with health literacy measurements, such as functional, interactive, and critical food literacy. This scale has acceptable reliability and validity. Health professionals can use this scale to analyze and improve food literacy in diabetic patients. This is a new instrument and thus far no questionnaire has been made to evaluate food literacy in diabetic patients.